Nkucetelo wa vukreste eka mafambisele ya muti wa ndhavuko wa mutsonga - Mhinga, M. E. (University of Limpopo, 2012)
Chapter 1: This deals with the introduction, background to the problem, aim of the study, the significance of the study, definition of terms, methodology, scope of the research and literature review. Chapter 2: Outlines the changes that occurred in the Tsonga traditional family focusing on the building of the dwellings, courtyard, kraals, fowlrun, due to the influence of Christianity among the Vatsonga people.Chapter 3: Outlines the resources that were used in the Mutsonga family and looking again on how the family lived before being affected by the impact of Christianity amongst them. Chapter 4: Outlines the changes that occurred in the Mutsonga family with the focus on how it was run, how traditional leadership was portrayed, the Vatsonga dresscode, their traditional beliefs, education and health, the division of labour as well as the traditional food that the Vatsonga people took pride in, due to the impact of Christianity on them. Chapter 5: Deals with conclusion wherein the findings and recommendations have been outlined.
The influence of Christianity in the running of the mutsonga traditional family
Thesis (M.A. (African Languages)) -- University of Limpopo, 2012
Keywords: Christianity; Tsonga tradition; Tsonga (African people); Cristianity -- Influence